COMMUNICATIONS ACTIVITIES. MARCH 1990 (900300). (Tufts Archival Research Center, 2007)
Copy; Summary of communications activities for March 1990. Includes media tours by consultants focusing on air quality issues and the social costs of smoking. Discusses Citizens for Tax Justice media events, as well as American Federation of Government Employees activities. Mentions individual meetings, articles and speeches in regards to excise tax, indoor air quality, and smoking restrictions. Summarizes the Congressional Hearing on the tobacco and alcohol industry targeting of youth, women and minorities.